La contabilidad como instrumento de un adecuado crecimiento y desarrollo económico-financiero de una microempresa. - Villate Paredes, Roberto Carlos (2012)
Since Peru is a country where there is poverty and high unemployment, the MSEs are to become an important alternative for generating employment and wealth. It is therefore an imperative need to continue to actively promote business development of small and medium businesses (MYPES) from the state that continue to include them as an unavoidable part of national development policy and that schools, especially the economic faculties of universities in the country, deeply involved in the training of entrepreneurs by vocation to go shaping a new generation of entrepreneurs Peruvian national development needs. We can say that the MYPES have become an innovative force in the national and global economy, mainly due to the drive and perseverance of its workforce. But such administrative problems faced mainly due to the lack of entrepreneurial culture that have owners or partners of these companies this shortcoming is reflected often in unfavorable results in the economic - financial authorities said. It is here where accounting professionals can contribute significantly in projecting results. All this constitutes a challenge for accountants, it is the accounting professional who can diagnose major weaknesses of a company and is also the accountant who can find alternative solutions for these and likewise found the main strengths that help MYPES to growth and sustainable development.